2017
DOI: 10.12688/f1000research.10101.1
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the cutaneous porphyrias

Abstract: This is an overview of the cutaneous porphyrias. It is a narrative review based on the published literature and my personal experience; it is not based on a formal systematic search of the literature. The cutaneous porphyrias are a diverse group of conditions due to inherited or acquired enzyme defects in the porphyrin–haem biosynthetic pathway. All the cutaneous porphyrias can have (either as a consequence of the porphyria or as part of the cause of the porphyria) involvement of other organs as well as the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 62 publications
0
28
0
1
Order By: Relevance
“…Some products containing titanium dioxide might be of benefit. 54 , 55 Some data have shown beta carotene therapy to be effective in reducing skin symptoms, although in a controlled study this effect has been shown to be minimal. 56 …”
Section: Cutaneous Porphyriasmentioning
confidence: 99%
“…Some products containing titanium dioxide might be of benefit. 54 , 55 Some data have shown beta carotene therapy to be effective in reducing skin symptoms, although in a controlled study this effect has been shown to be minimal. 56 …”
Section: Cutaneous Porphyriasmentioning
confidence: 99%
“…In patients with iron overload, phlebotomy is an accepted treatment and unnecessary sources of iron should be stopped. The raised ALAT is a typical finding in patients with active PCT, due to a concomitant liver involvement (1,6). It can also be related to hemochromatosis (7).…”
mentioning
confidence: 96%
“…In PCT phototoxic heme precursors accumulate and lead to blisters and erosions on light-exposed areas (1)(2)(3)(4)(5). The healing process is slow and the sores typically heal with scars.…”
mentioning
confidence: 99%
See 2 more Smart Citations